Meteorological study of the high sulphate and nitrate wet deposition episodes in Ontario, vol. 3. Report No. ARB-164-91 - "Srivastava, B"; "Yap, D"; "Reid, N W" (1992)
This volume three of the report contains Appendix II and III. Appendix II describes the narratives of 33 (nos. 2.1 to 2.33) high SO4 and NO3 wet deposition episodes in 1986 at Chalk River, Dorset, Longwoods (AES), and Longwoods (MOE). Each narrative describes the meteorological conditions yielding various types of precipitation in the area of the station, 72-hour backward air trajectories at 1000 mb, 925 mb, 850 mb, and 700 mb levels, and a brief summary. Appendix III includes the transport index to quantify the source-receptor analysis.
Keywords: "54 ENVIRONMENTAL SCIENCES"; "NITRATES"; "DEPOSITION"; "ONTARIO"; "AIR QUALITY"; "SULFATES"; "AIR"; "CHALK RIVER"; "LEVELS"; "MAPS"; "METEOROLOGY"; "PRECIPITATION"; "TRAJECTORIES"; "TRANSPORT"; "CANADA"; "DEVELOPED COUNTRIES"; "ENVIRONMENTAL QUALITY"; "FLUIDS"; "GASES"; "NITROGEN COMPOUNDS"; "NORTH AMERICA"; "OXYGEN COMPOUNDS"; "SEPARATION PROCESSES"; "SULFUR COMPOUNDS"; "540120* - Environment, Atmospheric- Chemicals Monitoring & Transport- (1990-)"